2010
DOI: 10.1080/15374411003691735
|View full text |Cite
|
Sign up to set email alerts
|

Positive Illusory Bias and Response to Behavioral Treatment Among Children with Attention-Deficit/Hyperactivity Disorder

Abstract: The current study investigates the accuracy of self-perceptions of competence among 43 children with attention-deficit/hyperactivity disorder (ages 6.9-11.9; 37 boys) attending an 8-week empirically supported behavioral summer treatment program. Having inflated self-perceptions about one's competence at the beginning of the summer predicted poorer response to the intervention administered in the program as assessed by changes in observed conduct problems, peer-nominated social preference, and friendship. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 43 publications
3
65
0
Order By: Relevance
“…Thus, the PIB may be an obstacle to instigating independent selfimprovement in areas that are needed most, and indeed, there is evidence that the PIB is associated with poor treatment outcome (Mikami et al 2010). This may be especially true for children with ADHD plus ODD, as their negative and hostile attitude towards others may be worsened or maintained by an overly positive self-view.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, the PIB may be an obstacle to instigating independent selfimprovement in areas that are needed most, and indeed, there is evidence that the PIB is associated with poor treatment outcome (Mikami et al 2010). This may be especially true for children with ADHD plus ODD, as their negative and hostile attitude towards others may be worsened or maintained by an overly positive self-view.…”
Section: Discussionmentioning
confidence: 97%
“…Such research in ADHD samples is especially pressing given that acknowledging one's challenges may predict psychosocial treatment success. For example, Mikami et al (2010) recently reported that the PIB was negatively associated with psychosocial treatment outcome for children with ADHD.…”
mentioning
confidence: 97%
“…Moreover, a recent study with 172 children with ADHD found that poorer teacher-reported social self-control was associated with children's greater externalizing behavior, which was then linked to receiving fewer "like most" nominations from peers [38]. Other research suggests that social cognitive deficits such as poor perspective taking skills, reduced empathy, theory of mind problems, overestimation of one's own social competence, social information processing biases, and sensation seeking goals may also contribute to the peer problems of children with ADHD [41][42][43][44][45]. These findings are essential to understanding how problem behaviors and social skills deficits in children with ADHD lead to peer rejection.…”
Section: Historical Conceptualizations Of Peer Problems In Adhdmentioning
confidence: 99%
“…There is only one study that investigated the influence of treatment on the PIB of children with ADHD. The results showed that intensive cognitive behavioral interventions failed to alter this bias (Mikami et al, 2010). This raises the question of which are the interventions that could reduce the PIB.…”
Section: Discussionmentioning
confidence: 77%
“…The study of self-perception in ADHD children shows that self-concept and its bias must be taken into account in the treatment of this disorder. Both, for its impact on the child's functioning, and for its effect on the treatment itself, since there is evidence that over-positive self-perceptions are associated with poorer treatment outcomes (Mikami, Calhoun, & Abikoff, 2010).…”
Section: Discussionmentioning
confidence: 99%